Performances dissidentes e ciberespaço: a monstruosidade como deslocamento do eu online - Barreto, Rafaela Gomes Paes (2023)
Dissident artistic performances carried out online were the starting point for investigating possible contributions of this artistic language to the reflection on the production of subjectivity intertwined with digital technologies. The concept of cyberspace, in turn, served to understand the dynamics of the internet network and how social network media operate in this environment, weaving dialogues between the role of social network and the production of a subject with the implications that this relationship causes in the body, a category that was placed under analysis. Dissident performances were taken as an umbrella concept as it was used to refer to singular artistic expressions that intentionally make displacements regarding gender, sexuality, race, humanity, disability, among other markers that falsify the unity called body. With regards to methodology, the research adopted cartography, using an online navigation log as a data collection tool to analyze the proposed profiles. Based on the data collected in the profiles, we will then conduct an analysis in dialogue with texts by authors such as Donna Haraway, Jeffrey Jerome Cohen, Tomaz Tadeu Silva, Paul Preciado, and others that may be known throughout the text. In this perspective, it was of interest to point out similarities and differences in the intersections of these phenomena and the effects for the contemporary subject, bringing such performances carried out on the internet closer to the phenomenon of the monster and the cyborg, thinking both as phenomena of subjectivity production. In conclusion, dissident performances highlight the importance of rethinking subjectivity and identity by challenging dominant societal narratives present in the cyberspace by proposing a shift in perspective and raising new questions about the circulation of the body in this field.